The influence of leader member exchange and organizational culture on organizational citizenship behavior (OCB) with organizational commitment as a mediating variable - Shelly, Shelly; Barkah, Barkah; Daud, Ilzar; Shalahuddin, Ahmad; Fauzan, Rizky (Enrichment : Journal of Management, 2023)
Every company has several factors that become a strong foundation as a basis for advancing the success of the company. This study aims to statistically test and provide empirical information about the effect of Leader Member Exchange (LMX) and Organizational Culture on Organizational Citizenship Behavior (OCB) with Organizational Commitment as a mediating variable with the object of research of 230 respondents of PT Hartono Plantation Indonesia employees determined by purposive sampling technique. The data analysis technique used in this research is Structural Equation Modeling (SEM) with AMOS software. The test results show that there is a positive and significant effect on each variable partially (individually) or the mediating effect